Analysis of Integrated Marketing Communication Strategies in Building Brand Awareness During Pandemic (Case Study : Rajutan Nyonya SME, Semarang) - Arauna Wangsa Elsha Dara; Lina Sinatra Wijaya (Enrichment : Journal of Management, 2022)
The pandemic period had an impact on the economic sector in Indonesia, which experienced a decline in sales, especially for Small and Medium Enterprises (SMEs). In contrast to the Rajutan Nyonya Semarang, which has succeeded in developing its business through innovations carried out by implementing an integrated marketing communication strategy. The implementation of this strategy can build public brand awareness of the product. This study uses a qualitative descriptive approach and SWOT analysis. The aim is to find out the marketing communication strategies used by Rajutan Nyonya Semarang in building brand awareness during the pandemic. The results in this study are the application of marketing communication concepts which consist of Direct Marketing, Sales Promotion, Public Relations, Personal Selling, Advertising, Word of Mouth Marketing (WOM), and Event and Experiences. In the interactive marketing strategy, Rajutan Nyonya Semarang has not utilized it optimally on social media. The results of interviews with informants show that the brand of Rajutan Nyonya has been at the Top of Mind level. Referring to the results of the study, it can be concluded that the implementation of an integrated marketing communication strategy carried out by Rajutan Nyonya Semarang to build brand awareness has been successful. This can be achieved because of the strength of recommendations from the community and efforts in satisfying customers through quality products and excellent service. However, there are suggestions for the business owner to be more active in using features on social media and broaden knowledge about digital media.